THE ROLE OF INTERNATIONAL LAW AND NATIONAL LAW IN HANDLING MARINE PLASTIC LITTER - Andreas Pramudianto (Lampung Journal of International Law, 2019)
The spread of marine plastic litter is increasing and dangerous for habitats and marine living such as the discovery of plastic in fish, sea turtles, whale mammals and even seabirds. To suppress and reduce plastic waste in the sea, one of them is to strengthen the role of law both international, regional and national law. The research objective is to analyze international, regional and national law in the perspective of international law sources to deal with marine plastic litter. The research method in this study is an analytical description based on a normative juridical approach. The results of the study show that international law in the perspective of international law sources has attempted to regulate plastic waste in the sea even though it is limited. Handling of marine plastic litter does not yet have comprehensive regulations or regulated separately. In the other hand, national law becomes important in handling at the respective jurisdiction boundaries, although limited in the application of rules due to the existence of national jurisdiction. Provisional conclusions show that international law still has an important role to play especially in relation to marine plastic litter that crosses national borders or outside national jurisdiction.